Management of urban stormwater at sub-watershed level - Arora, Amarpreet Singh (My University, 2015)
This thesis presents the outcomes of a comprehensive research study undertaken to investigate the quantity and quality of stormwater generated from the urban areas. The outcome of the information obtained has been utilized in developing a sub-watershed level urban stormwater management system. Urban stormwater quantity and quality from five different urban sub-watersheds (that differ in land use and development activities) was investigated in the city of Patiala, India. The five sub-watersheds have similar geological, topographical and climatic conditions and were chosen to minimize the effect of these characteristics on stormwater quality and quantity. Assessment on the quantity of stormwater generated was made using Hydrological methods. For characterization, stormwater samples were collected during twelve storm events between April 2010 and March 2013 and analyzed for various water quality parameters. Results of the investigation indicate a strong correlation between land use and development activities and the resulting stormwater quality. TSS, COD, Total Coliform, Fecal Coliform, Oil and Grease,and heavy metals (Fe and Pb) were found to be major pollutants in surface runoff generated from commercial and urbanized catchments (all exceeded the Inland surface water quality standards developed by Central Pollution Control Board, India). The water quality of the smaller residential catchment was better as compared to other catchments. Principal component analysis was investigated to identify linkages between stormwater quality and urban surface types. Possible inter-parameter relationships among different water quality parameters were identified which was subsequently used in deciding on the scheme of the stormwater treatment system. Multivariate data analysis technique was used to investigate the influence of antecedent dry days and average rainfall intensity on stormwater quality,through regression analysis. Regression models were developed to assess the characteristics of stormwater runoff produced from any specific storm event with specified antecedent dry days. Information obtained via quantification and characterization was used in developing a sub-watershed level urban stormwater management system involving collection, treatment and disposal system. An experimental treatment system was developed to test the treatment efficiency of the system in removing pollutants present in the stormwater. Protocol of the ground water recharge facility was also developed. The primary objective of this research work was to create fundamental knowledge on the quantity and quality of stormwater, to utilize this information in developing an adequate stormwater management system addressing an integrated approach to collection, treatment and disposal. The outcomes of this research can provide practical information for improved urban water management.
PHD, DBT
Keywords: urban stormwater; regression modeling; characterization; biotechnology; DBT